System-Ergonomic Design of Cognitive Automation Dual-Mode Cognitive Design of Vehicle Guidance and Control Work Systems - Onken, Reiner. (Studies in Computational Intelligence,, 2010)
Why this book? Simply because it is due. Cognitive automation and its system-ergonomic introduction into work systems have been advanced in the meantime to such a degree that already applications for operational work systems are slowly becoming reality. This book shall contribute to give system designers some more guidelines about designing work systems and associated cognitive machines effectively, in particular those related to guidance and control of manned and unmanned vehicles. The issue is that the findings on cognition have to become sufficient commonsense for all from the various disciplines involved in system design, and that guidelines are given how to make use of it in an appropriate and systematic manner. These guidelines are to account for both the needs of the human operator in the work process and the use of computational potentials to make the work system a really most effective one. In other words, this book is meant to provide guidelines for the organisational and technical design of work systems. Therefore, this book is an interdisciplinary one. Findings in individual disciplines are not the main issue. It is rather the combination of these findings for the sake of the performance of work systems which makes this book a useful one for designers who are interested in this modern approach and its implementation.